(untitled) (Revista Tópos, 2013)
Este artigo apresenta uma discussão, baseada em revisão literária, sobre a importância de se planejar e aplicar metodologias participativas que envolvam a comunidade, onde os estudos são realizados, e a comunidade científica, com o intuito de dar relevância científica e social às pesquisas desenvolvidas. Essas metodologias participativas são pensadas no âmbito de estudos arqueológicos e museológicos, com iniciativas de Educação Patrimonial junto à comunidade local. Nesse sentido, apresenta propostas participativas pensadas em estudos arqueológicos desenvolvidos, atualmente, na região do Vale do Paranapanema, lado paulista, no município de Iepê- SP. Palavras-Chave: Educação Patrimonial; Arqueologia; Comunidade Local. ARCHAEOLOGY AND EDUCATIONAL HERITAGE Abstract This article presents a discussion, based on literary revision, on the importance of planning and applying participative methodology and applying participative methodology that could involve the community where the studies were carried on, and also the scientific community, aiming at pointing out scientific and social relevance to the research developed. This participative methodology was thought over in the field of archaeological and museological studies, with the initiative of Educational Heritage within the local community. In this sense, it presents participative propositions thought over in archaeological studies, currently developed in the region of Paranapanema Valley, on São Paulo, side, in the County of Iepê, SP. Key words: educational heritage, archaeology, local community.